2012
DOI: 10.1186/1748-717x-7-154
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of sunitinib, a multi-tyrosine kinase inhibitor, as a radiosensitizer for human prostate cancer

Abstract: BackgroundMany prostate cancers demonstrate an increased expression of growth factor receptors such as vascular endothelial growth factor receptor (VEGFR) and platelet derived growth factor receptor (PDGFR) which have been correlated with increased resistance to radiotherapy and poor prognosis in other tumors. Therefore, response to radiation could potentially be improved by using inhibitors of these abnormally activated pathways. We have investigated the radiosensitizing effects of sunitinib, a potent, multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
9
27
0
Order By: Relevance
“…In a preclinical evaluation of sunitinib as a radiosensitizer for human prostate cancer, Brooks and colleagues concluded that sunitinib and radiation therapy do not interact directly to radiosensitize PC3 tumor cells in vivo (22). However, the fact that there was additional delay in tumor growth suggested that sunitinib may be acting on the tumor stroma by suppressing its ability to sustain regrowth from the irradiated tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In a preclinical evaluation of sunitinib as a radiosensitizer for human prostate cancer, Brooks and colleagues concluded that sunitinib and radiation therapy do not interact directly to radiosensitize PC3 tumor cells in vivo (22). However, the fact that there was additional delay in tumor growth suggested that sunitinib may be acting on the tumor stroma by suppressing its ability to sustain regrowth from the irradiated tumor.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, small chemical inhibitors of PDGF-D have not been developed so far with proven anti-tumor efficacy in humans. Because PDGF-D exerts its function via activation of its receptor PDGFR-β, multiple small molecule tyrosine kinase inhibitors that inactivate PDGFR have been reported 102105 . For example, imatinib, a tyrosine kinase inhibitor that interferes with the phosphorylation and activation of PDGFRβ, has been reported to inhibit cell growth and invasion in various cancer cell lines 106 .…”
Section: Pdgf-d As a Cancer Therapeutic Targetmentioning
confidence: 99%
“…Sunitinib, a multi-tyrosine kinase inhibitor, reduces survival and migration of human meningioma cells by targeting PDGFR 107 . Moreover, Sunitinib could serve as radiosensitizer for human prostate cancer partly through the inhibition of PDGFR and VEGFR 102 . ABT-348 exerts its anti-tumor activity via targeting the VEGFR, PDGFR, Aurora, and SRC kinase 103 .…”
Section: Pdgf-d As a Cancer Therapeutic Targetmentioning
confidence: 99%
“…Sunitinib is an orally bioavailable multi-tyrosine kinase receptor inhibitor with potent activity against VEGFR and PDGFR that has demonstrated enhanced efficacy of radiation therapy in experimental pre-clinical models [1011]. Combined PDGFR and VEGFR inhibitor therapy facilitated optimal antiangiogenic and antiproliferative effects of radiation in prostate cancer and glioma models compared to either inhibitor alone [12].…”
Section: Introductionmentioning
confidence: 99%